An itinerary through the enigmatic and credible paths of the barquisimetan popular wisdom (Mayéutica Revista Científica de Humanidades y Artes, 2023)
The legend is a type of short story which represents some singnificant events in a community’s oral tradition, besides having fantastic events and encourages values from a generation to another. This article postulates an approximation to the semiotichermeneutical analysis of five legends from Barquisimeto, these were selected from the Catálogo del Patrimonio Cultural Venezolano de la región occidental, municipio Iribarren (2005). Theoretical basis were based on Morote (2005) who defined legend, Todorov (1981 y 1992) about hermeneutics, Eco (1986) in relation to semiotics and symbols’ meaning according to Cirlot (1992), Chevalier (1986) and BruceMitford (1997) and Speech Acts (Searle, 1994). Among the results it is possible to say thenext: (a) the causes present in legends is deaths’ returning, (b) The macro act of speech present are information and warning and (c) Death, struggle between good and evil and sins represent Barquisimetan people worries.
Keywords: Sgemiotic hermeneutical analysis; Barquisimetan legend; symbols